Entrepreneurial Skills Required for Self-Employment among Electrical Installation Students in Technical Colleges in Adamawa State: A Focus on Managerial, Accounting, and Marketing Competencies - Joseph Zambwa; Ishaya Tumba; Rabiu Akila Falama (Journal of Corporate Finance Management and Banking System, 2024)
This study investigates the entrepreneurial skills required by Electrical Installation and Maintenance Works (EIMW) trade students in Government Science and Technical Colleges in Adamawa State for successful self-employment. Utilizing a descriptive survey research design, data were collected from a sample of 217 respondents, including administrators, teachers, and students, using a structured questionnaire. The findings reveal that students need a total of 20 managerial skills, with particular emphasis on effective planning and resource control. Additionally, the study identifies 22 essential accounting skills, such as determining profit and loss and knowledge of costing, which are crucial for business survival. In terms of marketing, students require 16 key skills, highlighting the importance of customer loyalty retention and effective communication. These findings emphasize the necessity for educational institutions to enhance their curricula by integrating practical entrepreneurial training. The study also recommends collaboration with local businesses to provide students with real-world experiences and continuous professional development for educators to ensure they are equipped to teach relevant skills.